Resilient City Strategies for Urban Waste Management: A Case Study of Lubuklinggau City, Indonesia - Mohammad Nur Dita Nugroho; Jatmiko Yogopriyatno; Abdul Hamid Hakim; Abdul Aziz Zulhakim; Amin Shody Ashary (Utan Kayu Publishing, 2025)
Urban waste management in Lubuklinggau City, Indonesia, encounters systemic challenges, including limited service coverage, insufficient infrastructure, low levels of public participation, and weak integration between technical regulations and spatial planning. This study explores context-specific strategies aimed at strengthening urban resilience within waste governance systems. Utilizing an exploratory mixed-methods approach, the research integrates SWOT analysis with the Analytical Hierarchy Process (AHP) to identify and prioritize strategic alternatives. Data were collected through field observations, reviews of regional regulations, spatial planning documents, and institutional reports. Twelve strategic options were developed from internal and external factors, then organized hierarchically and weighted through pairwise comparison. Findings indicate that the highest-priority strategy involves accelerating the formulation of technical regional regulations aligned with spatial and fiscal planning frameworks (priority weight = 0.229), followed by the development of a controlled landfill system supported by public-private partnerships (PPP) and corporate social responsibility (CSR) initiatives. The AHP model achieved a consistency ratio of 0.054, confirming the model’s logical validity. The study concludes that regulatory reform, cross-sectoral coordination, and community-based initiatives are critical to enhancing the adaptive capacity of medium-sized cities. These findings offer theoretical contributions to resilient city frameworks and practical insights for urban regions facing institutional and environmental challenges.